Baclofen Combined With Psychosocial Care is Useful and Safe in Alcohol-Related Cirrhosis Patients: A Real-Life Multicenter Study. (16th December 2022) - Barrault, Camille; Alqallaf, Shuaib; Lison, Hortensia; Lamote-Chaouche, Isabelle; Bourcier, Valérie; Laugier, Joëlle; Thevenot, Thierry; Labarriere, Damien; Ripault, Marie-Pierre; Le Gruyer, Antonia; Costentin, Charlotte; Behar, Véronique; et al.
Abstract: Background: Alcohol-related cirrhosis is a frequent and difficult-to-treat disease. Despite the low hepatic metabolism of baclofen, data on its use in this subgroup are scarce. The French multicenter Observatory of patients treated with Baclofen for Alcohol DEpendence real-life cohort assessed: (a) prescription modalities of baclofen in liver units; (b) safety profile of baclofen; and (c) declared alcohol intake, biological markers of excessive alcohol intake and hepatic function at 12 months. Methods: All consecutive patients with cirrhosis who received baclofen to reduce alcohol consumption or maintain abstinence were prospectively included. Psychosocial management was always associated. Clinical and biological data were collected every 3 months for 1 year. Results: Between November 2013 and December 2016, 71 in- or outpatients were included from 10 liver units. Of the patients, 25% had ascites. After 12 months, 52 patients (73%) were still being followed, and 41 (57.7%) were still receiving baclofen at a mean dosage of 75 mg/day (r30-210). The overall declared consumption decreased from 100.2 to 14.7 g/day ( P < 0.0001), and 29 patients (40.8%) reached abstinence. Significant improvement in the usual biomarkers of excessive alcohol intake (AST, GGT and MCV) and liver function (Prothrombin ratio (PTr), albumin levels) were observed. The usual side effects such as drowsiness were frequent (22%) but no serious adverse events (AEs) or overt encephalopathy related to baclofen was reported. Conclusion: In this 1-year follow-up series, baclofen was combined with psychosocial treatment in patients with cirrhosis and was well tolerated. This treatment was associated with a significant decrease in declared alcohol consumption as well as improvement in hepatic function. Abstract : Short Summary: In this series of 71 patients with alcohol-related cirrhosis, 12 months' baclofen use at a dose of 75 mg/day associated with psycho-social care was well tolerated and associated with the improvement of liver function.